Time-evolution of poly(3-hexylthiophene) as an energy relay dye in dye-sensitized solar cells. - Humphry-Baker, N; Driscoll, K; Rao, A; Torres, T; Snaith, H; Friend, R (2012)
Energy relay dyes (ERD) and Förster resonant energy transfer (FRET) are useful techniques for increasing absorption in dye-sensitized solar cells. We use femtosecond transient absorption spectroscopy to monitor charge generation processes in a solid-state DSC containing poly(3-hexylthiophene) (P3HT) as both the hole-transporter and the ERD with a zinc phthalocyanine dye (TT1) as the sensitizer. We observe efficient FRET occurring on picosecond time scales and subsequent hole transfer from TT1 to P3HT occurring onward from 100 ps.